Determination of the capacity of removal of cadmium by Salvinia auriculata Aubl. in polluted water (Revista Científica Ciencias Naturales y Ambientales, 2019)
Cadmium is considered one of the most dangerous heavy metals, its high toxicity has generated various problems to the environment and the health of living beings. The aim of this work was to demonstrate the ability to remove Cd by Salvinia auriculata in contaminated water and record the morphological effects due to its exposure. For this, S. auriculata was exposed to 5 dilution treatments of 0, 0.25, 0.5, 1 and 2 mg / L Cd for 8 days. At the end of the bioassay, the biomass, the percentage of tolerance, the average length of the leaves was determined and photographs of those were taken. Water and plant tissue samples were analyzed by atomic absorption spectrophotometry of graphite furnace. The removal results found were 64%, 56%, 55% and 53% for 0.25, 0.5, 1 and 2 mg / L Cd, respectively. Regarding the effects, inhibition of growth, chlorosis and alteration of the edge of the leaves was observed in all treatments with Cd. In plants exposed to 2 mg / L Cd, partial necrosis and damage to the trichomes were observed. Despite toxicity symptoms, S. auriculata was able to maintain high percentages of Cd removal. The controlled culture of S. auriculata is proposed for the removal of Cd in contaminated water and its use as a bioindicator of this metal.
Keywords: Cadmium; Phytoremediation; Removal; Salvinia auriculata